2014
DOI: 10.1186/s12888-014-0281-0
|View full text |Cite
|
Sign up to set email alerts
|

Exploring psychosis and bipolar disorder in women: a critical review of the qualitative literature

Abstract: BackgroundThe experiences of women with severe mental illness warrant particular consideration to identify the strategies they use to facilitate recovery. This review systematically examined women’s experiences of psychosis and bipolar disorder.MethodsFollowing an extensive database search, 13 studies met inclusion criteria. Noblit and Hare’s metasynthesis approach was used to synthesise these qualitative studies exploring the experiences of 250 women, of which 78 (31.2%) were also mothers.ResultsTwelve sub-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Perceived loss has featured in previous reviews relating to severe maternal mental health disorders (Smith et al 2018;Wittkowski et al 2014;Dolman et al 2013). However, for women and families experiencing PP, the sense of loss was pervasive and reported across multiple domains of women's lives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perceived loss has featured in previous reviews relating to severe maternal mental health disorders (Smith et al 2018;Wittkowski et al 2014;Dolman et al 2013). However, for women and families experiencing PP, the sense of loss was pervasive and reported across multiple domains of women's lives.…”
Section: Discussionmentioning
confidence: 99%
“…Previous metasyntheses have explored individuals' experiences of serious mental health problems and mental health services in the postnatal period (Ruffell et al 2019;Smith et al 2018;Plunkett et al 2016;Megnin-Viggars et al 2015;Wittkowski et al 2014;Dolman et al 2013). However, given the range of maternal mental health disorders included in those reviews, the applicability of these findings to women's experiences of PP remains unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The women participants drew upon cultural understandings in order to form complex and nuanced accounts of their difficulties (see also Marriott et al, 2018) and develop culturally appropriate coping strategies. Spiritual beliefs are inextricably linked to modes of understanding and strategies of coping with psychotic experiences, and in the studies conducted in Western societies these seem to characterize more women belonging to migrant and minority groups with stronger religious and spiritual affiliations (Wittkowski et al, 2014).…”
Section: Women Femininity Sexuality and Psychosismentioning
confidence: 99%
“…A more recent critical review of the qualitative literature on women with BD, summarizing 13 studies, identified six strategies used to cope with the disorder (which is similar, but not identical to coping with stress): (a) finding motivation in the parental role, (b) seeking support from social networks, (c) seeking support from professionals, (d) hiding the disorder by attempting to appear “normal,” (e) taking medication, and (f) seeking alternatives to conventional treatment, including, among others, religious or spiritual practices and yoga ( Wittkowski, McGrath, & Peters, ). Lawn and McMahon () used qualitative methods to explore, for example, gender differences in the experience of 28 partners (9 men) married to people contending with a wide range of severe mental disorders (but not specifically BD).…”
mentioning
confidence: 99%